Pelatihan Penyusunan Soal Berbasis HOTS Di Sekolah Menengah Pertama Muhammadiyah 02 Bojonegoro - Santoso, Subhan Adi; Mustafidah, Nur Mashani; Susanto, Arif (Conscilience: Jurnal Penelitian dan Pengabdian Masyarakat, 2024)
This learning expects students to achieve various competencies by implementing HOTS or High Level Thinking Skills. These competencies are critical thinking, creativity and innovation, communication skills, collaboration skills and self-confidence. So this service activity aims to build teacher skills in preparing HOTS-based questions at Muhammadiyah 02 Bojonegoro Junior High School. Service activities are carried out in the form of offline training at the Muhammadiyah 02 Bojonegoro Junior High School location. The results of the service show that there is an increase in the teacher's ability in preparing HOTS-based questions as an effort to increase teacher competence in the learning assessment process in the classroom.